Noninvasive stimulation of prefrontal cortex strengthens existing episodic memories and reduces forgetting in the elderly - Sandrini, Marco; Brambilla, Michela; Manenti, Rosa; Rosini, Sandra; Cohen, Leonardo G.; Cotelli, Maria (Frontiers in Aging Neuroscience, 2014)
Memory consolidation is a dynamic process. Reactivation of consolidated memories by a reminder triggers reconsolidation, a time-limited period during which existing memories can be modified (i.e. weakened or strengthened). Episodic memory refers to our ability to recall specific past events about what happened, including where and when. Difficulties in this form of long-term memory commonly occur in healthy aging. Because episodic memory is critical for daily life functioning, the development of effective interventions to reduce memory loss in elderly individuals is of great importance. A previous study in young adults showed that the dorsolateral prefrontal cortex (DLPFC) plays a causal role in strengthening of verbal episodic memories through reconsolidation. The aim of the present study was to explore the extent to which facilitatory transcranial direct current stimulation (anodal tDCS) over the left DLPFC would strengthen existing episodic memories through reconsolidation in elderly individuals. On Day 1, older adults learned a list of 20 words. On Day 2 (24h later), they received a reminder or not, and after 10 minutes tDCS was applied over the left DLPFC. Memory recall was tested on Day 3 (48h later) and Day 30 (1 month later). Surprisingly, anodal tDCS over the left DLPFC (i.e. with or without the reminder) strengthened existing verbal episodic memories and reduced forgetting compared to sham stimulation. These results provide a framework for testing the hypothesis that facilitatory tDCS of prefrontal cortex might strengthen existing episodic memories and reduce memory loss in older adults with amnesic mild cognitive impairment.